Microbial community composition of a multi-stage moving bed biofilm reactor and its interaction with kinetic model parameters estimation. - Wang, Xiaodong; Bi, Xuejun; Hem, Lars John; Ratnaweera, Harsha (Journal of Environmental Management, 2018)
Microbial community diversity determines the function of each chamber of multi-stage moving bed biofilm reactor (MBBR) systems. How the microbial community data can be further used to serve wastewater treatment process modelling and optimization has been rarely studied. In this study, a MBBR system was set up to investigate the microbial community diversity of biofilm in each functional chamber. The compositions of microbial community of biofilm from different chambers of MBBR were quantified by high-throughput sequencing. Significantly higher proportion of autotrophs were found in the second aerobic chamber (15.4%), while 4.3% autotrophs were found in the first aerobic chamber. Autotrophs in anoxic chamber were negligible. Moreover, ratios of active heterotrophic biomass and autotrophic biomass (X H /X A ) were obtained by performing respiration tests. By setting heterotroph/autotroph ratios obtained from sequencing analysis equal to X H /X A , a novel approach for kinetic model parameters estimation was developed. This work not only investigated microbial community of MBBR system, but also it provided an approach to make further use of molecular microbiology analysis results.